Pelatihan Aplikasi Augmented Reality Bagi Guru Bidang Studi IPS Untuk Menunjang Pembelajaran Digital Di Kota Makassar - Hasni; Syawaluddin, Ahmad; Padli, Feri; Rusdi (Ininnawa : Jurnal Pengabdian Masyarakat, 2024)
In today's digital era, information and communication technology has become an integral part of the learning process. One promising innovation in education is Augmented Reality (AR), which can improve learners' interaction and understanding of the subject matter. Augmented Reality (AR) application training for Social Science (IPS) teachers in SMP Makassar City aims to improve teachers' knowledge and skills in utilizing AR technology to support digital learning. This activity was carried out for three days with the method of introducing theory, practicing the use of applications, and preparing AR-based learning materials. The training results show significant improvements in teachers' knowledge and skills, as well as motivation to use technology in learning. However, there are challenges related to infrastructure and resistance to change. Therefore, continuous support is needed for the implementation of AR in learning.